2017
DOI: 10.1016/j.molcel.2017.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Mutant p53 Gains Its Function via c-Myc Activation upon CDK4 Phosphorylation at Serine 249 and Consequent PIN1 Binding

Abstract: TP53 missense mutations significantly influence the development and progression of various human cancers via their gain of new functions (GOF) through different mechanisms. Here we report a unique mechanism underlying the GOF of p53-R249S (p53-RS), a p53 mutant frequently detected in human hepatocellular carcinoma (HCC) that is highly related to hepatitis B infection and aflatoxin B1. A CDK inhibitor blocks p53-RS's nuclear translocation in HCC, whereas CDK4 interacts with p53-RS in the G1/S phase of the cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
105
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(111 citation statements)
references
References 63 publications
6
105
0
Order By: Relevance
“…12 However, It is well known that different CDK play distinct roles in different tumor cell cycles. 13 For the first time, we discovered through a serum starvation experiment that CDK2 was consistent with the trend of SEPT2 from the early G1 phase ( Figure 1A). Subsequently, the expression of CDK2 and SEPT2 in different cell cycles was analyzed using the double thymidine synchronization method.…”
Section: Correlated Dynamic Expression Of Cyclindependent Kinase 2 supporting
confidence: 52%
See 1 more Smart Citation
“…12 However, It is well known that different CDK play distinct roles in different tumor cell cycles. 13 For the first time, we discovered through a serum starvation experiment that CDK2 was consistent with the trend of SEPT2 from the early G1 phase ( Figure 1A). Subsequently, the expression of CDK2 and SEPT2 in different cell cycles was analyzed using the double thymidine synchronization method.…”
Section: Correlated Dynamic Expression Of Cyclindependent Kinase 2 supporting
confidence: 52%
“…Studies have suggested that NEDD5 (SEPT2) is not only expressed in all brain tumors but also changes with the cell cycle progression, reaching a peak in the G2/M phase . However, It is well known that different CDK play distinct roles in different tumor cell cycles . For the first time, we discovered through a serum starvation experiment that CDK2 was consistent with the trend of SEPT2 from the early G1 phase (Figure A).…”
Section: Resultsmentioning
confidence: 54%
“…In cancer cells expressing GOF mutant p53, groups of genes that belong to the CBP (39), NRF2 (40), c-MYC (41, 42), ETS1/2 (43, 44), networks as well as those that are involved in chromatin methylation/acetylation (MLL1/2, MOZ; 45) are transactivated (mtp53 reviewed in 38, 4446). Preferential binding of ETS1 to WTp53 and ETS2 to mtp53 have been reported, suggesting tumor-suppressive function for the former and oncogenic function for the latter, which is discussed in this review.…”
Section: Introductionmentioning
confidence: 99%
“…The prolyl isomerase PIN1, a critical modifier of multiple signaling pathways, is overactivated in cancers, and it promotes cancer and cancer stem cells by disrupting the balance of oncogenes and tumor suppressors (28)(29)(30)(31). Inactivation of PIN1 function conversely curbs tumor growth and cancer stem cell expansion, restores chemosensitivity, and blocks metastatic spread, thus providing a rationale for a therapeutic strategy based on PIN1 inhibition (32)(33)(34). However, the available PIN1 inhibitors either lack the required specificity and potency or cannot efficiently enter cells to inhibit PIN1 function in vivo (35).…”
Section: Discussionmentioning
confidence: 99%